Annealing-Induced Modifications in Physicochemical and Optoelectronic Properties of Ag-Doped Nanostructured CdS Thin Films - Vidya S. Taur; Rajesh A. Joshi; Ramphal Sharma (International Journal of Photoenergy)
The Ag-doped nanostructured CdS thin films are grown by simple, cost effective chemical ion exchange technique at room temperature on ITO-coated glass substrate. These as grown thin films are annealed at 100, 200, 300, and 400°C in air atmosphere for 1 hour. To study the effect of annealing on physicochemical and optoelectronic properties, these as grown and annealed thin films are characterized for structural, compositional, morphological, optical, and electrical properties. X-ray diffraction (XRD) pattern reveals polycrystalline nature of these thin films with increase in crystallite size from 6.4 to 11.2 nm, from XRD the direct identification of Ag doping in CdS thin films cannot be judged, while shift in characteristics peak position of CdS is observed. The Raman spectrum represents increase in full width at half maxima and intensity of characteristic peak, confirming the material modification upon annealing treatment. Presence of Cd, Ag, and S in energy dispersive X-ray analysis spectra (EDAX) confirms expected elemental composition in thin films. Scanning electron microscopy (SEM) images represent grain growth and agglomeration upon annealing. Red shift in optical absorbance strength and energy band gap values from 2.28 to 2.14 eV is obtained. I-V response obtained from as grown and annealed thin films shows an enhancement in photosensitivity from 72% to 96% upon illumination to 100 mW/cm2 light source.